Evaluation of The Factors Affecting the Choice of Profession of The Dental Students - Dogan, Mehmet Emin; Kotanli, Sedef; Yavuz, Yasemin (Indonesian Journal of Dental Medicine, 2022)
Background: Researches on motivation of students to choose dentistry as a profession has been conducted for many years. Students may choose to become dentists for reasons such as serving, being independent, working with their hands, gaining prestige, and financial security. Purpose: The aim of this study is to evaluate the factors in the career preferences of dental students, their expectations and opinions in the education process. Methods: 1,007 participants who answered the web-based questionnaire were included in this study. Obtained data were analysed using SPSS version 23.0 (Inc., Chicago, IL, USA). The Independent t test was used for intergroup comparisons in the data were normally distributed. Variables in more than two groups were compared using the one-way ANOVA test. Statistical significance was accepted as p<0.05 in all analyses. Results: A total of 1007 dentistry students, 370 (36.7%) male and 637 (63.3%) female, with a mean age of 21.15 ± 1.96 participated in the survey study. 236 (23.4%) of the participants were in the first grade, 236 (23.4%) in the second grade, 192 (19.1%) in the third grade, 261 (25.9%) in the fourth grade, and 82 (8.1%) in the fifth grade. 44% of the participants chose the option 'they want to be medicine or dentistry, but gaining dentistry because of their score in the university entrance exam' as the reason for choosing dentistry. Conclusion: Such studies will be useful for the procedures to be followed in eliminating stress and anxiety in students and in the pre-detection of problems.